The Effective Executive: The Definitive Guide to Getting the Right Things Done - Girdharwal, Nitin (Indian Journal of Marketing, 2020)
Management books usually deal with managing other people. The subject of the book, The Effective Executive: The Definitive Guide to Getting the Right Things Done is managing oneself for effectiveness. Without a doubt, officials who don’t oversee themselves for viability can’t in any way, shape, or form hope to deal with their subordinates. Managers who donâ€™t have an idea of how to make themselves effective in their own activity and work set the wrong example. To be sensibly successful, it is not sufficient for the person to be intelligent, to work hard, or to be educated. Effectiveness is something independent, something else. Be that as it may, to be viable additionally does not require unique endowments, exceptional inclination, or extraordinary preparing. Effectiveness as an executive requires doing certain- and genuinely basic-things. It comprises of few practices, the practices that are introduced and talked about in this book.